2021
DOI: 10.3390/su132111749
|View full text |Cite
|
Sign up to set email alerts
|

Student Satisfaction with Online Learning during the COVID-19 Pandemic: A Study at State Universities in Sri Lanka

Abstract: This quantitative study investigated the determinants of students’ satisfaction with their online learning experience at Sri Lankan universities during the COVID-19 pandemic. The data was collected from 1376 undergraduates enrolled in various courses in humanities and social sciences at three state-owned universities in the country. The results of the Structural Equation Modeling (SEM) revealed that the independent variables of the model, namely perceived learner motivation, perceived challenges of e-learning,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 56 publications
4
39
0
Order By: Relevance
“…Alternatively, besides Tomlinson's (2017) conceptualization, our target students' academic accomplishments, in light of SOL, are aligned with previous student self-efficacy research (Prior et al, 2016;Shen et al, 2013), which have shown a connection between selfefficacy and academic success using online platforms (Hettiarachchi et al, 2021). Quantitatively, our students perceived the ultimate outcome of SOL for their developmental collaboration and spirits (M = 3.670).…”
Section: Research Questionsupporting
confidence: 74%
See 3 more Smart Citations
“…Alternatively, besides Tomlinson's (2017) conceptualization, our target students' academic accomplishments, in light of SOL, are aligned with previous student self-efficacy research (Prior et al, 2016;Shen et al, 2013), which have shown a connection between selfefficacy and academic success using online platforms (Hettiarachchi et al, 2021). Quantitatively, our students perceived the ultimate outcome of SOL for their developmental collaboration and spirits (M = 3.670).…”
Section: Research Questionsupporting
confidence: 74%
“…Secondly, perceived growth was also a noticeable aspect, suggesting that the students further developed their knowledge, attitudes, and behaviors in response to the available resources on the distant learning platforms (Tomlinson, 2017). Our findings were reflective of the students' strong confidence and sense of regulated learning placed into the learning process (Hettiarachchi et al, 2021). The students gained disciplinary knowledge in a number of ways, had appropriate attitudes towards learning, and actively engaged in e-learning, as benefiting from an educationally-digital learning environment (Li, 2021;Varenin et al, 2021).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…There are several research projects conducted worldwide regarding online teaching and learning, particularly after the outbreak of the COVID-19 pandemic [6,8,26,[28][29][30][31][32][33][34][35][36]. However, most of these research papers are based on quantitative studies, particularly on survey of students.…”
Section: Teaching and Learning During The Covid-19mentioning
confidence: 99%